KETAKUTAN 1965 SEBAGAI KETAKUTAN MASA KINI: Menelaah Ketakutan Sekuler, Agama dan Supranatural - Justin L Wejak (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2015)
This paper investigates how Indonesian Catholics living in outlying areas in eastern Indonesia experience fear in relation to the events that have arisen from the massacre of suspected Indonesian communists in 1965. It is concerned with why the Catholic Church created an image of communists as fear-inspiring beings, and how this fear was maintained after the communists had been largely eliminated through the state-sponsored killings of 1965/66. The object of inquiry is a historical document produced in 1967 by the Catholic Church that sought to explain events leading up to 1965. This paper analyses the forces that underlie this fear in terms of the secular fear of communism, the religious fear of Islamic fanaticism, and the supernatural fear of communist ghosts as a result of the killing of communists in 1965. It argues that the fear of 1965 is not a matter of the past but part of the present, an argument that is in accordance with Martin Heidegger’s contention that all fears are concerned with the present. Keywords: Ketakutan, Katolik, komunis, Islam, hantu, sekuler, agama, supranatural.